CONTROL OF ELECTRIC MOTOR USING BLUETOOTH - Bhadane, Pravin; Patil, Pooja; Singh, Nisha; Mishra, Priya (International Journal of Computer Sciences and Engineering, 2025)
Switching the control of an electric motor with help of a Bluetooth device has been carried out in the present work. Electric motor works on electricity whose supply is controlled by a mechanical switch. In the present work switch is replaced by electronically operated transistor which is further controlled by a smart phone with help of a Bluetooth device. The wireless control action is achieved by assembling the prototype device which includes Bluetooth module, microcontroller, transistor and electric motor. A simple self explanatory software program is written for controlling the on/off action of motor. Present work is helpful for the beginners as well as first year student of computer science.